Exploring the Medicine and Shaman Paradigm Shift for Game “Dukun Start-Up” Through Pixel Art Style - Faizal Akbar; Pratama Bayu (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This study addresses the lack of culturally meaningful visual representations in Indonesian indie games, with a particular focus on the implementation of the pixel art style for the game